Colonization of porcine intestine by enterotoxigenic Escherichia coli: selection of piliated forms in vivo, adhesion of piliated forms to epithelial cells in vitro, and incidence of a pilus antigen among porcine enteropathogenic E. coli. - Nagy, B (Infect Immun, 1977)
In contrast to K88-positive porcine enterotoxigenic Escherichia coli (ETEC), K88-negative porcine ETEC strains did not adhere to isolated intestinal epithelial cells in vitro. However, they did adhere to intestinal epithelium in vivo. Growth of one such ETEC (strain 987) in pig small intestine consistently yielded a greater percentage of piliated cells than did growth in vitro. This increase was demonstrable by electron microscopy, by change in colonial morphology, and by agglutination in specific antisera against the pili of strain 987. In contrast to the stored stock culture (which contained very few piliated cells), richly piliated forms of strain 987 did adhere to isolated intestinal epithelial cells in vitro. A series of porcine E. coli strains was tested for agglutinability in antiserum against the pili of strain 987, and several K88-negative ETEC strains were agglutinated. These data are consistent with the hypothesis that pili facilitate intestinal adhesion and colonization by K88-negative ETEC strains. IMAGES: